Rapid parameter identification and control of an induction machine. Issue 5 (26th September 2018) - Nell, Martin Marco; von Pfingsten, Georg; Hameyer, Kay
Abstract : Purpose: Traction applications, e.g. the IMs are mainly operated by field-oriented control (FOC). This control technique requires an accurate knowledge of the machine's parameters, such as the main inductance, the leakage inductances and the stator and rotor resistance. The accuracy of the parameters influences the precision of the calculated rotor flux and the rotor flux angle and the decoupling of the machine's equations into the direct and quadrature coordinate system (dq-components). Furthermore, the parameters are used to configure the controllers of the FOC system and therefore influence the dynamic behavior and stability of the control. Design/methodology/approach: In this paper, three different methods to calculate the machine's parameters, in an automated and rapid procedure with minimal measuring expenditure, are analyzed and compared. Moreover, a method to configure a control that reduces the overall Ohmic losses of the machine in every torque speed operation point is presented. The machine control is configured only with the identified machine parameter. Findings: Simulations and test bench measurements show that the evolutionary strategy is able to identify the electrical parameters of the machine in less time and with low error. Moreover, the controller is able to control the torque of the machine with a deviation of less than 2 per cent. Originality/value: The most significant contribution of the research is the potential to identify the machine parameter of an induction motor and to configure an accurate control with these parameters.